The effect of distal‐end trimming on Saccharina latissima morphology, composition, and productivity. Issue 5 (21st June 2021) - Grebe, Gretchen S.; Byron, Carrie J.; Brady, Damian C.; St. Gelais, Adam T.; Costa‐Pierce, Barry A.
Abstract: As kelp cultivation increases around the world, so does the need for farm management strategies that produce specific crop characteristics, optimize yield, widen harvesting windows, and prevent biomass loss. Distal‐end trimming of macroalgae has been recommended as a farm management method addressing these needs. In this study, we trimmed cultivated Saccharina latissima sporophytes grown in the Western Gulf of Maine (WGoM) to 60 cm above the stipe–blade interface. We characterized the effect of trimming on the morphology, tissue nutrient content, stable isotope ratio, and nitrate reductase activity of the kelp. We also evaluated the economic trade‐offs of trimming using a simple production model. The results suggest that trimming the blade to 60 cm may have minimal biological consequences. Additionally, the trimming appears to benefit "short" kelp blades in proximity to the trimmed blades. Daily yield (% increase in weight day −1 ) after trimming was initially lower than the control, but late‐season daily yields and crop‐retention following storms were markedly improved. Ultimately, we conclude that growers could use trimming to acquire kelp biomass earlier in the season, retain late‐season biomass, and potentially increase the total revenue gained from kelp farming if price premiums can be exacted for this biomass.